Factors Influencing Indonesian Women Becomes Migrant Workers - Hussin, Mutia Hariati (Universitas Muhammadiyah Yogyakarta, 2013)
This paper describes how the Indonesian women, despite the fact that some migrant workers are economically and politically poorly protected by the state, kept the desire to try their luck as migrant workers abroad. In almost all economic sectors, both formal and non-formal, many of the Indonesian Female Migrant Workers (FMW/TKW) living and working abroad did not receive their full rights as workers and sometimes even lost their basic rights such as that to minimum wage, not having their wages, withheld or not paid at all as well as refusal to have their passports returned. Many of the Indonesian TKWs were even physically and sexually abused by their employers while many female workers were victimized into becoming forced prostitutes by their sponsors. In addition, some of the TKW had to face serious problems of protection; many as victims of corrupt practices such as the imposition of illegal levy by the Indonesian and the receiving country police and immigration staffs; demands for payments, extortion of money and confiscation of valuables. Noting that, despite all the sufferings, the numbers of migrant workers are constantly increasing, this paper analyzes the causal mechanism of female migration from the socioeconomic and political context in Indonesia.